EFEKTIVITAS PEMBELAJARAN MENDALAM DITINJAU DARI KEMAMPUAN BERPIKIR KOMPUTASIONAL DALAM PELAJARAN MATEMATIKA PADA SISWA SEKOLAH DASAR - Arifin, Nurdin; Adianto, Samsul; Wahyuningrum, Retno; Jannah, Nur Aulia Miftahul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to determine the effectiveness of deep learninh from the mathematical computational thingking ability of students at SD Negeri 004 North Samarinda. Based on the results of observations made at SD Negeri 004 Nort Samarinda, there is a problem namely the lack of students’ mathematical computational thingking skills during the learning process. The reseacrh methode is a pre-experiment with a pretest-posttest one group design. The results obtained after the treatment mere given increased with an average student test of 83, so the students’ mathematical computational thingking ability was good. Based on test 1 one sample t-Test the average score of the students’ mathematical computational thingking ability tes tis more than 70. The results of test 2, namely the proportion test, stated that more than 75% of students got a score of more than 70. The test results of the 3 paired sample t-Test average on the posttest score are more than the pretest score. Thus deep learning is effectively reviewed from the mathematical computational thingking ability of students.